La prueba pericial psicológica en los delitos de violencia contra la mujer y su valoración en la decisión judicial en Santo Domingo, 2024 - Tacle Toapanta, Anthony Ariel (2025)
This article analyzed the psychological expert evidence in crimes of violence against women, focusing on its judicial assessment in Santo Domingo during 2024. The objective of the research was to design a legal study on the importance of psychological expert evidence as an evidentiary means in cases of psychological violence against women and family members. The study was developed using a qualitative-quantitative approach of a transversal type. It was directed through a random probabilistic sampling investigating 80 legal professionals from the Ecuadorian Association of Female Lawyers, along with interviews with two judges, an expert, a prosecutor, and a review of statistical data from the Integrated Fiscal Procedures System (SIAF) – General State Prosecutor's Office Analytics. The main results show that the effectiveness rate of complaints is minimal, with only one conviction out of 1,750 cases. Judges argue that while psychological expert evidence is essential, it is not sufficient by itself to determine criminal responsibility. To establish the materiality of the offense and the culpability of the accused, other evidentiary means, such as documents and testimonies, are required. 66.7% of the professionals surveyed state that psychological expert evidence greatly influences judicial decisions in these cases. Based on these findings, it is concluded that psychological expertise is one of the main pieces of evidence because it allows for the objective determination of the emotional impact on the victim, providing technical support that strengthens judicial decisions.